O totalitarismo enquanto negação da política: o terreno fértil para o domínio total e as suas implicações no Direito - Cidrão, Ênio Stefani Rodrigues Cardoso (2024)
Totalitarian regimes, consolidated in the first half of the 19th century, possess characteristics that are fertile for philosophical reflection. The theorist Hannah Arendt developed her work around the theme of political experience and the drama of these events. Mass murder and the distortion of the logic of the normative system awaken thought to the mechanisms used by totalitarianism to establish itself, in order to guarantee the adhesion and passivity of society as a whole. How, then, does the totalitarian suppression of political participation occur to the point of reaching the incapacity of joint organization of individuals? Thus, the objective is to understand the context that proved to be propitious for the totalitarian phenomenon in terms of its aspect of negation of the political dimension of the human condition. The research is carried out through the deductive and dialectical method, taking into account the application of concepts and the consideration of the social context in which the facts under analysis are involved, and uses bibliographic and documentary sources, having the Arendtian study on totalitarianism as a paradigm of understanding. It is concluded that totalitarianism, although unprecedented in history, crystallized elements that, over time, had been taking shape, as observed in the historical process by which man sees himself completely detached from community ties and the factual world in which he appears to his fellow men and realizes his political potentialities. Despite the fact that total domination has been installed in an overwhelming way, the subtlety of the social context that gave it space is what deserves attention so that barbarism does not return in a subtle way to the contemporary scenario, and the Arendtian idea of having the right to have rights should be taken as a guide, as a guarantee of effective insertion in an organized political community.